Enhancing small business success through effective tax management and policy optimization - Netto, Aylton José; Ferreira, Fabiana de Sá (Revista Sistemática, 2024)
The examination of fiscal practices and challenges faced by small businesses underscores the pivotal role of effective tax management in their success and growth. Tax deductions, which allow businesses to reduce taxable income by subtracting certain expenses, are essential tools that help alleviate financial pressures. Despite their potential benefits, many small business owners struggle due to insufficient tax planning and the need for meticulous financial record-keeping. The reviewed studies reveal a significant need to optimize tax policies to support small business development. For instance, proposals such as the Standard Business Deduction (SBD) aim to simplify the tax process by providing a fixed amount that can be claimed above the line, reducing the need for detailed expense tracking and potentially lowering compliance and enforcement costs. Additionally, recommendations for improving accounting practices highlight the importance of simplifying and standardizing accounting requirements to meet informational needs and enhance efficiency. Further research indicates that tailoring tax policies to specific sectors, such as agriculture, can address the unique challenges faced by small businesses in these areas. Effective tax planning and a well-organized accounting system are crucial for maximizing tax benefits and enabling productive investment in business growth. Overall, the intersection of business structure, tax systems, and accounting organization is critical for the effective operation of small enterprises. Future research should focus on refining these areas to provide solutions that support the sustainable development and prosperity of small businesses.